Development and performance evaluation of alkali-intercalated nano-porous carbons materials from waste plastics for CO2 capture applications - Alamro, Mohammed (2025)
The global imperative to mitigate greenhouse gas emissions and address climate change necessitates the development of advanced carbon capture technologies. This PhD research explores the valorisation of polymeric waste materials—including polyurethane (PU), polyisocyanurate (PIR), phenolic resin (PR), and mixed foams—into high-performance activated carbons (ACs) for post-combustion CO2 capture. Using sustainable carbonization-activation methods with KOH and K2CO3 as activating agents, the study demonstrates the potential of these waste-derived materials as cost-effective, efficient, and scalable adsorbents under industrially relevant flue gas conditions.